2020
DOI: 10.1002/cnm.3337
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of spiral‐flow inflow boundary conditions when using idealized artery geometries in the analysis of liver radioembolization: A parametric study

Abstract: In the last decades, the numerical studies on hemodynamics have become a valuable explorative scientific tool. The very first studies were done over idealized geometries, but as numerical methods and the power of computers have become more affordable, the studies tend to be patient specific. We apply the study to the numerical analysis of tumor‐targeting during liver radioembolization (RE). RE is a treatment for liver cancer, and is performed by injecting radiolabeled microspheres via a catheter placed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…A three‐dimensional idealised geometry of the hepatic artery was used in this study, as shown in Figure 1. This type of arterial geometry can be used as a generalist approach that allows for the independent analysis of the effect of a variable in the microsphere distribution with respect to others 17 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A three‐dimensional idealised geometry of the hepatic artery was used in this study, as shown in Figure 1. This type of arterial geometry can be used as a generalist approach that allows for the independent analysis of the effect of a variable in the microsphere distribution with respect to others 17 …”
Section: Methodsmentioning
confidence: 99%
“…To further analyse the particle dispersion on a surface of interest, an index is defined to evaluate the degree to which the particles are spread out in the artery lumen in the simulations, denoted as the coefficient of variation, CoV, as explained in 17 . This index represents the ratio between the standard deviation, σ , and the average, trueX¯, of the particles located in the cells at a specific cross‐section of the artery and is defined by Equation (16): CoVgoodbreak=σXtrue¯0.25em The particle concentration in a group of cells in a specific cross‐section of the artery is determined by the unsteady statistics variable accumulative particles in cell , ϕ , defined in ANSYS® Fluent 19.2 24…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood has been assumed to have a density of 1060 kg/m 3 [ 12 , 18 , 21 25 , 27 , 29 32 ] or 1050 kg/m 3 [ 10 , 13 17 , 20 , 26 , 33 , 34 , 37 ]. Blood densities around 1050 kg/m 3 have been measured in the arterial level, decreasing to a value of 1040 kg/m 3 at the capillary level [ 38 ].…”
Section: Modeling Approaches To Study Rementioning
confidence: 99%